Improved hydrogen storage properties of LiBH4 via nanoconfinement in micro- and mesoporous aerogel-like carbon. (6th April 2016) - Surrey, Alexander; Bonatto Minella, Christian; Fechler, Nina; Antonietti, Markus; Grafe, Hans-Joachim; Schultz, Ludwig; Rellinghaus, Bernd
Abstract: Herein, we present the effect of the nanoconfinement of LiBH4 within porous aerogel-like carbon on its hydrogen storage properties. The carbon scaffold is prepared by salt templating – a facile and sustainable technique for the production of micro- and mesoporous carbon-based materials. A loading of up to 40 wt. % of LiBH4 is achieved by melt infiltration, and the hydride remains amorphous as shown by differential scanning calorimetry (DSC), X-ray diffractometry (XRD) and scanning transmission electron microscopy (STEM). Simultaneous thermogravimetry and mass spectroscopy (TG-MS) reveal that the nanoconfined LiBH4 starts to desorb hydrogen already at 200 °C with the main release at 310 °C. A partial rehydrogenation at moderate conditions (100 bar and 300 °C) is demonstrated. In contrast to recent reports, in-situ heating in the transmission electron microscope (STEM) and electron energy loss spectroscopy (EELS) indicate that both decomposition products (B and LiH) remain within the carbon pores. Nuclear magnetic resonance (NMR) measurements reveal the presence of amorphous and partially oxidized boron in the dehydrogenated sample that may impede the reversibility of the (de)hydrogenation process. Highlights: Nanoconfinement of LiBH4 in micro- and mesoporous aerogel-like carbon is successfully realized via melt infiltration. Reduced hydrogen desorption temperature at 310 °C with an onset temperature of 200 °C. High LiBH4 loadings of 40–50 wt. %. Partial rehydrogenation is achieved under mild conditions (300 °C under 100 bar H2 for 3 h). No ejection of LiH from the carbon pores is observed by in-situ STEM heating experiments.